Transfusion of red blood cell concentrates in children at Brazzaville University Hospital: epidemiological, clinical, and biological aspects - Kambourou, Judicaël; Oko, Aymar Pierre Gildas; Mambou Pemba, Jevia Monica; Ocko Gokaba Letsho, Thibaut; Lombet, Léticia; Engoba, Moyen; Moyen, Georges Marius (International Journal of Contemporary Pediatrics, 2025)
Background: Objective was to study the transfusion practice of red blood cell concentrates (RBC) in children hospitalized in the pediatric departments of the Brazzaville University Hospital. Methods: A single-center analytical cross-sectional study on RBC transfusion in children was carried out between November 2022 and October 2023 in the pediatric departments of Brazzaville University Hospital Centre (B-UHC). Children aged 1 month to 17 years, hospitalized for severe anemia who had received a RGC transfusion were included. The study variables were sociodemographic, clinical, biological, those linked to blood transfusion (BT) of RBC and progressive. The Chi square test and odds ratio were used with significance at p<0.05. Results: A total of 300 patients (21.59%) were included, including 53% boys, sex ratio 1.13. The average age was 21.5 months (range 1 month and 17 years). Children aged 1 month to 5 years represented 49.3%. Sickle cell disease was the main cause of anemia: 57.6%. The average haemoglobin (Hb) level before transfusion was 5.9 g/dl. The most used blood was that of group O+. TS significantly improved Hb and hematocrit levels. Death occurred in 17% of cases linked to low socio-economic status (SES), a long time to transfusion and a Hb level <5 g/dl on admission. Conclusions: TS of RGCs remains a very frequent activity in the pediatric environment of the Brazzaville University Hospital in relation to the prevalence of severe anemia. The prevention of the main pathologies causing severe anemia as well as the strengthening of the capacities of the National Blood Transfusion Centre (NBTC) remain the essential therapeutic weapons.